Analisis Faktor-Faktor yang mempengaruhi Kinerja Keuangan Bank Umum Syariah yang terdaftar di Bursa Efek Indonesia (BEI) (Periode 2014-2016) - Hamdani Hamdani; Nining Wahyuni; Ali Amin; Sulfitra Sulfitra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2018)
This research is supposed the effect Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), (BOPO) Operating Expenses to Operating Income to Return on Asset (ROA) as a proxy of the Financial Performance of Islamic banking in Indonesia period 2014- 2016. The population in this study was 11 Islamic Bank in Indonesia in asset listed on Bursa Efek Indonesia for the period years 2014-2016, and the sample is got as 33 forms 11 banking and 3 periods financial report of 2014-2016 by purposive sampling method. The data analyses employed the use of multiple linear regression with Software SPSS version 16.0. The result from this study indicates that variable Financing to Deposit Ratio and Capital Adequacy Ratio has not significant influences on ROA, while BOPO variable has significant influences on ROA. Predictive ability of the three variables on the ROA of 72,3%, while the rest is influenced by other factors not included in the research model.